PGE2 downregulates LPS-induced inflammatory responses via the TLR4-NF-κB signaling pathway in bovine endometrial epithelial cells. (February 2018) - Shen, Yuan; Liu, Bo; Mao, Wei; Gao, Ruifeng; Feng, Shuang; Qian, Yinghong; Wu, Jindi; Zhang, Shuangyi; Gao, Long; Fu, Changqi; Li, Qianru; Deng, Yang; et al.
Abstract: Postpartum bacterial infections of the uterus cause endometritis in dairy cows. Inflammatory responses to bacterial infections in the bovine uterus were generated through pattern recognition receptors (PRRs) that bind to pathogen-associated molecules such as lipopolysaccharide (LPS) from Escherichia coli . Among these PRRs, Toll-like receptor 4 (TLR4) is primarily responsible for LPS recognition, which triggers inflammatory responses via mitogen-activated protein kinases (MAPKs) and NF-κB signaling activation, resulting in the expression of inflammatory mediators in mammals such as IL-8 and IL-6. Previous studies indicate that PGE2 plays an important role in bacterial endometritis, although details on the mechanism underlying how it regulates LPS-induced inflammatory responses in bovine endometrial epithelial cells (bEECs) remain elusive. In the present study, bEECs were pre-treated with exogenous PGE2 and/or PGF2α prior to LPS stimulation. With PGE2 pre-treatment, we observed an augmentation in LPS-stimulated PKA, ERK, and IκBα phosphorylation and cyclooxygenase-2 (COX-2) and anti-inflammatory cytokine IL-6 expression and downregulation of prostaglandin E2 receptor 4 (EP4) and TLR4 in bEECs. These results indicate that LPS-induced inflammatory responses through TLR4 signaling in bEECs could be downregulated by exogenous PGE2 pre-treatment, but not PGF2α . Highlights: IL-6 secretion in bEECs after LPS stimulation was enhanced by exogenous PGE2 . LPS-induced TLR4 and EP4 expression decreased after exogenous PGE2 treatment. PGE2 downregulates LPS-induced inflammatory responses in bEECs.